Meningkatkan Literasi Remaja melalui Edukasi Reproduksi yang Ramah Budaya di Murung Raya : Pengabdian - Dewi Nur Anita (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Adolescents in rural areas often face limited access to reproductive health information due to a lack of facilities and strong cultural norms that consider the issue taboo. Low reproductive health literacy can lead to risks of unwanted pregnancies, sexually transmitted infections, and other health problems. This community service initiative aims to improve reproductive health literacy among adolescents in Danau Usung Village through education based on local wisdom using culturally sensitive teaching modules. The community service was conducted in three stages: an initial survey to identify the level of adolescent literacy, the implementation of counseling and education based on modules containing Dayak folk tales, discussions with traditional leaders, and traditional games, and pre-test and post-test evaluations to assess improvements in literacy. There was a significant increase in adolescents' reproductive health literacy scores after the intervention, from an average of 54.6 to 82.3. Adolescents demonstrated better understanding and positive attitudes toward reproductive health issues. Education based on local wisdom effectively improved adolescents' reproductive health literacy. This strategy is recommended for implementation in areas with strong cultural values.